The Effect of Acupuncture Therapy on the Concentration Level of Health Students - Ayu Anom Rastiti, Ida; Ayu Suptika Strisanti, Ida; Rosa Tri Anggaraeni, Komang; Indrayoni, Putu (Jurnal Keterapian Fisik, 2024)
Background: Health students face various challenges during their studies. The demands of mastering clinical skills and the ability to build therapeutic relationships with patients require high concentration from health students. So it is important for health students to have good concentration during the learning process so that students' mastery of clinical skills can be achieved optimally. Acupuncture is a therapeutic modality that has been proven to have a function to improve individual cognitive abilities. This study aims to identify the effectiveness of acupuncture therapy in improving the concentration of health students. Methods: The research sample in this study is 60 undergraduate nursing students of the Institute of Technology and Health Bali who are divided into an intervention group (n = 30) and a control group (n = 30). The instrument that will be used in this study is the Grid Concentration test to assess the level of student concentration. Results: There was a significant increase (p < 0.05) in the concentration score in the treatment group, where before acupuncture the concentration score was (median = 14) and after acupuncture, the concentration score became (median = 20.50). Conclusion: According to the results above, it proves that acupuncture therapy is effective in improving student concentration and can directly optimize working memory capacity.